Second‐generation cryoballoon ablation for treatment of persistent atrial fibrillation: Three‐year outcome and predictors of recurrence after a single procedure. (10th November 2017) - Akkaya, Ersan; Berkowitsch, Alexander; Zaltsberg, Sergej; Greiss, Harald; Hamm, Christian W.; Sperzel, Johannes; Neumann, Thomas; Kuniss, Malte
Abstract: Introduction: Data on long‐term outcomes of cryoballoon (CB) ablation for treatment of persistent atrial fibrillation (AF) are sparse. Here, we report the first 3‐year follow‐up results and predictors of success for catheter ablation using the second‐generation CB in patients with persistent AF. Methods and results: For this prospective observational study, we enrolled 101 patients ablated with the second‐generation CB at our institution. The endpoint was the first documented recurrence (> 30 seconds) of AF, atrial flutter, or atrial tachycardia after a 3‐month blanking period. Follow‐up data were collected during outpatient clinic visits and included Holter‐ECG recordings. The impact of several variables on recurrence was evaluated by means of univariate and multivariate analyses and Cox proportional hazards regression models. After a median follow‐up of 37 (31 of 42) months, recurrence was documented in 30 patients (29.7%). The median procedure and fluoroscopy times were 120 (102 of 147) and 20 (16 of 27) minutes, respectively. Phrenic nerve palsy occurred in 2.0% of the patients. Among the 30 patients who experienced recurrence, 16 underwent repeat ablation in radiofrequency technique. Cox regression analysis showed that left atrial area > 21 cm 2 and AF history duration > 2 years independently predicted recurrence. Conclusions: Sinus rhythm was maintained in a substantial proportion of patients even 3 years after CB ablation. Patients with a nonenlarged left atrium and short AF history had the best outcome.